The The Effect of Preliminary Generational Leadership on The Interest of Continuing Family Business With Family Harmony as a Mediating Variable - Effendy, Junko Alessandro; Keitaro, Kedrick (Universitas Ciputra Surabaya, 2021)
Succession is one of the problems in the family business, where there are not many children who should be the next generation who are interested in continuing the family business. Researchers conducted a pre-survey of future generations who have an interest in continuing the family business and it turns out that leadership and family harmony are the two highest factors. The purpose of this study was to determine the relationship between leadership and interest in continuing the family business with family harmony as a mediation. Respondents of this study were 61 students of the family business curriculum who had reached their final semester. The results of the study indicate that leadership has an effect on family harmony, leadership does not affect the interest in continuing the family business, family harmony affects the interest in continuing the family business and is a variable that fully mediates the relationship between leadership and interest in continuing the family business.